Mapping Mapping the Development of Paradiplomacy Research through Bibliometric Analysis - Issundari, Sri; Yani, Yanyan Mochamad (Departemen Hubungan Internasional, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Padjadjaran, 2024)
The purpose of this paper was to analyze the bibliometric characteristics of articles on paradiplomacy published in Scopus-indexed by analyzing the development of paradiplomacy studies, the prominent authors with the most citations, and the prominent journals containing the most paradiplomacy studies. This research used a bibliometric and content analysis of publications in the Scopus database collected through Publish and Perish. By using VOSviewer, a total of 109 articles were analyzed by classifying title, abstract, and keywords. The findings show that trend of paradiplomacy research focuses on theoretical frameworks and paradiplomacy issues such as globalization, federalism, development, foreign policy, and interests. Future research may be focused on case studies and elaborating forms of paradiplomacy. The findings also indicate that Canada, the USA, and Europe still dominate paradiplomacy studies, but research from other areas may emerge in the future. The prominent author with the most citations is Noe Cornago, while the prominent journal contains the most paradiplomatic research is The Hague Journal of Diplomacy (HJD). The Conclusion is paradiplomacy research has increased significantly. Canada, the USA, and Europe are the largest contributors to paradiplomacy publications, but other regions such as Latin America, Asia, and Africa have also begun to focus on this study. Thus, Latin America, Asia, and Africa need to be more active in research on this topic by bringing up empirical practices experienced by themselves.